U.S. consumers demand for cash in the era of low interest rates and electronic payments - Tamás Briglevics; Scott Schuh (Federal Reserve Bank of Boston, 2013)
U.S. consumers' demand for cash is estimated with new panel micro data for 2008-2010 using econometric methodology similar to Mulligan and Sala-i-Martin (2000); Attanasio, Guiso, and Jappelli (2002); and Lippi and Secchi (2009). We extend the Baumol-Tobin model to allow for credit card payments and revolving debt, as in Sastry (1970). With interest rates near zero, cash demand by consumers using credit cards for convenience (without revolving debt) has the same small, negative, interest elasticity as estimated in earlier periods and with broader money measures. However, cash demand by consumers using credit cards to borrow (with revolving debt) is interest inelastic. These findings may have aggregate implications for the welfare cost of inflation because then nontrivial share of consumers who revolve credit card debt are less likely to switch from cash to credit. In the 21st century, consumers get cash from bank and nonbank sources with heterogeneous transactions costs, so withdrawal location is essential to identify cash demand properly.
Keywords: E41; E42; 330; cash demand; Baumol-Tobin model; Survey of Consumer Payment Choice; SCPC